3(m-2)=2(m-2)

Simple and best practice solution for 3(m-2)=2(m-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(m-2)=2(m-2) equation:



3(m-2)=2(m-2)
We move all terms to the left:
3(m-2)-(2(m-2))=0
We multiply parentheses
3m-(2(m-2))-6=0
We calculate terms in parentheses: -(2(m-2)), so:
2(m-2)
We multiply parentheses
2m-4
Back to the equation:
-(2m-4)
We get rid of parentheses
3m-2m+4-6=0
We add all the numbers together, and all the variables
m-2=0
We move all terms containing m to the left, all other terms to the right
m=2

See similar equations:

| (3q+2)^2=0 | | 6x2+10x+4=0 | | 110=6+1/2l | | f(2.5)=2.5^2-2.5-6 | | -5b+24=+1 | | b^-2=(2/3.5) | | 4x-1=53-3x | | b^-2=4 | | 14=6l-5 | | -7-8y=56 | | -5x-4.8=67 | | 3x^2-120x+640=0 | | 25x^2-2x+16=-42x | | xx9=117 | | 4t-2=214 | | (3/2)x-4=13 | | x+1÷3=x÷6 | | 917=9•x | | 6x-6-2x=0 | | 5^x^2-12=25^x | | 5c=c^2-6 | | V=1/2x4x0.5x2= | | (2x+4)(2x-4)=4x^2 | | 2x=1=9 | | 8x*4(4x-3)=4(6x+4)-4 | | 1/15b=-4.05 | | 3(-8-y)-2y-7=18 | | x/0.4=0 | | 2(x+6)^3=24 | | 21-4x+24x+45=2 | | 6×m=90 | | 4x+14+3x-12=180 |

Equations solver categories